Physical activity and metabolic health in chronic kidney disease: a cross-sectional study. Issue 1 (December 2016) - Bowlby, Wilson; Zelnick, Leila; Henry, Connor; Himmelfarb, Jonathan; Kahn, Steven; Kestenbaum, Bryan; Robinson-Cohen, Cassianne; Utzschneider, Kristina; de Boer, Ian
Abstract Background Patients with chronic kidney disease (CKD) are at high risk of progression to end stage renal disease and cardiovascular events. Physical activity may reduce these risks by improving metabolic health. We tested associations of physical activity with central components of metabolic health among people with moderate-severe non-diabetic CKD. Methods We performed a cross-sectional study of 47 people with CKD (estimated GFR <60 ml/min/1.73 m2 ) and 29 healthy control subjects. Accelerometry was used to measured physical activity over 7 days, the hyperinsulinemic-euglycemic clamp was used to measure insulin sensitivity, and DXA was used to measured fat mass. We tested associations of physical activity with insulin sensitivity, fat mass, blood pressure, serum lipid concentrations, and serum high sensitivity C-reactive protein concentration using multivariable linear regression, adjusting for possible confounding factors. Results Participants with CKD were less active than participants without CKD (mean (SD) 468.1 (233.1) versus 662.3 (292.5) counts per minute) and had lower insulin sensitivity (4.1 (2.1) versus 5.2 (2.0 (mg/min)/(μU/mL)), higher fat mass (32.0 (11.4) versus 29.4 (14.8) kg), and higher triglyceride concentrations (153.2 (91.6) versus 99.6 (66.8) mg/dL). With adjustment for demographics, comorbidity, medications, and estimated GFR, each two-fold higher level of physical activity was associated with a 0.9 (mg/min)/(μU/mL) higher insulin sensitivity (95% CI 0.2, 1.5, p  = 0.006), an 8.0 kg lower fat mass (−12.9, −3.1, p  = 0.001), and a 37.9 mg/dL lower triglyceride concentration (−71.9, −3.9, p  = 0.03). Associations of physical activity with insulin sensitivity and triglycerides did not differ significantly by CKD status (p -values for interaction >0.3). Conclusions Greater physical activity is associated with multiple manifestations of metabolic health among people with moderate-severe CKD.